Allogenic Stem Cells in Spinal Fusion: A Systematic Review. Issue 1 (May 2019) - Hsieh, Patrick C.; Buser, Zorica; Skelly, Andrea C.; Brodt, Erika D.; Brodke, Darrel; Meisel, Hans-Joerg; Park, Jong-Beom; Yoon, S. Tim; Wang, Jeffrey C.
Study Design: Systematic review. Objectives: To review, critically appraise, and synthesize evidence on the use of allogenic stem cell products for spine fusion compared with other bone graft materials. Methods: Systematic searches of PubMed/MEDLINE, through October 31, 2018 and of EMBASE andClinicalTrials.gov through April 13, 2018 were conducted for literature comparing allogenic stem cell sources for fusion in the lumbar or cervical spine with other fusion methods. In the absence of comparative studies, case series of ≥10 patients were considered. Results: From 382 potentially relevant citations identified, 6 publications on lumbar fusion and 5 on cervical fusion met the inclusion criteria. For lumbar arthrodesis, mean Oswestry Disability Index (ODI), visual analogue scale (VAS) pain score, and fusion rates were similar for anterior lumbar interbody fusion (ALIF) using allogenic multipotent adult progenitor cells (Map3) versus recombinant human bone morphogenetic protein–2 (rhBMP-2) in the one comparative lumbar study (90% vs 92%). Across case series of allogenic stem cell products, function and pain were improved relative to baseline and fusion occurred in ≥90% of patients at ≥12 months. For cervical arthrodesis across case series, stem cell products improved function and pain compared with baseline at various time frames. In a retrospective cohort study fusion rates were not statistically different for Osteocel compared with Vertigraft allograft (88% vs 95%). Fusion rates varied across time frames and intervention products in case series. Conclusions: The overall quality (strength) of evidence of effectiveness and safety of allogenic stem cells products for lumbar and cervical arthrodesis was very low, meaning that we have very little confidence that the effects seen are reflective of the true effects.